Identification and characterization of the ergochrome gene cluster in the plant pathogenic fungus Claviceps purpurea. Issue 1 (December 2016) - Neubauer, Lisa; Dopstadt, Julian; Humpf, Hans-Ulrich; Tudzynski, Paul
Abstract Background Claviceps purpurea is a phytopathogenic fungus infecting a broad range of grasses including economically important cereal crop plants. The infection cycle ends with the formation of the typical purple-black pigmented sclerotia containing the toxic ergot alkaloids. Besides these ergot alkaloids little is known about the secondary metabolism of the fungus. Red anthraquinone derivatives and yellow xanthone dimers (ergochromes) have been isolated from sclerotia and described as ergot pigments, but the corresponding gene cluster has remained unknown. Fungal pigments gain increasing interest for example as environmentally friendly alternatives to existing dyes. Furthermore, several pigments show biological activities and may have some pharmaceutical value. Results This study identified the gene cluster responsible for the synthesis of the ergot pigments. Overexpression of the cluster-specific transcription factor led to activation of the gene cluster and to the production of several known ergot pigments. Knock out of the cluster key enzyme, a nonreducing polyketide synthase, clearly showed that this cluster is responsible for the production of red anthraquinones as well as yellow ergochromes. Furthermore, a tentative biosynthetic pathway for the ergot pigments is proposed. By changing the culture conditions, pigment production was activated in axenic culture so that high concentration of phosphate and low concentration of sucrose induced pigment syntheses. Conclusions This is the first functional analysis of a secondary metabolite gene cluster in the ergot fungus besides that for the classical ergot alkaloids. We demonstrated that this gene cluster is responsible for the typical purple-black color of the ergot sclerotia and showed that the red and yellow ergot pigments are products of the same biosynthetic pathway. Activation of the gene cluster in axenic culture opened up new possibilities for biotechnological applications like the dye production or the development of new pharmaceuticals.